Analyzing factors influencing land utilization for food production among rural landowners in Ga-Mphahlele Village - Kamogelo Morwatshoge Maruma; Rudzani Nengovhela; Jan Johannes Hlongwane (Indonesian Journal of Agricultural Research, 2026)
Land plays a crucial role in ensuring food production and supporting rural livelihoods in South Africa. However, in Ga-Mphahlele Village, a significant portion of land owned by rural households remains underutilized, leading to reduced food production. This study aimed to analyze factors influencing land utilization for food production among rural landowners in Ga-Mphahlele Village, Limpopo Province. Primary data were collected from 75 rural landowners using structured questionnaires and face-to-face interviews. Descriptive statistics were used to describe socio-economic characteristics and land utilization patterns, while a binary logistic regression model was applied to determine factors influencing land utilization for food production. The results showed that only 41% of respondents actively utilized their land for food production, while 59% did not. The average age of respondents was approximately 60 years, reflecting an aging farming population.  Age, employment status, marital status, access to agricultural extension services, soil fertility, and type of farming equipment were found to influence land utilization significantly. Access to extension services was highly significant, highlighting the importance of institutional support in promoting land utilization. The study concludes that strengthening extension services, improving soil fertility management, supporting vulnerable households, and facilitating access to modern farming equipment can significantly increase and enhance land utilization for food production among rural landowners. These findings provide evidence-based insights for policymakers to design targeted interventions aimed at strengthening rural food production and livelihoods.